Etlingera (Zingiberaceae) in Bogor Botanic Gardens: Potential Benefits and Its Conservation Status - Novitasari, Yeyen (Jurnal Riset Biologi dan Aplikasinya, 2023)
Indonesia is one of mega biodiverse countries in the world, with a high global biodiversity index and many vascular plant species. However, not all plant species are known in terms of their uses, potential benefits, and conservation status. One of example is genus Etlingera, where further studies are required. Therefore, this study aimed to provide information on the potential benefits and uses of the genus Etlingera and to investigate its conservation status. The study was conducted using the method of literature study, an inventory of potential uses, and an inventory of the genus Etlingera living in Bogor Botanic Gardens through direct observation. Six species of the genus Etlingera were collected from the Bogor Botanic Gardens, namely Etlingera brevilabrum, E. elatior, E. hemisphaerica, E. loerzingii, E. megalocheilos, and E. walang, conservation status of three species (E. brevilabrum, E. hemisphaerica, and E. megalocheilos) is Least Concern (LC), two species (E. elatior and E. walang) are Data Deficient (DD), and one species (E. loerzingii) is Vulnerable (VU). All species are commonly used as spices, condiments, cosmetics, and traditional medicine to cure various diseases, possibly also as ornamental plants. The secondary metabolites present in some species, namely E. brevilabrum, E. elatior, and E. hemisphaerica can be used as antimicrobial, antifungal, and antioxidant agents.